THE STRATEGY OF DA’WAH BIL HAL COMMUNICATION: LITERATURE REVIEW - Reka Gunawan; Abdul Muhid (Universitas Islam Negeri Mataram, 2022)
Islam is a religion that assigns its people to broadcast and disseminate Islam to each other, therefore Islam is also called the religion of da’wah. Da’wah bil hal is da’wah with an emphasis on concrete actions, not just saying but also giving an example as a good figure. Following good communication, it will make it easier for preachers to preach. This study aims to find out the forms of the communication strategy of da’wah bil hal. The method in this study uses literature review as qualitative research. The results prove that the practical forms of the communication strategy of da’wah bil hal are divided into four, namely the strategy of da’wah bil hal through communication, the strategy of da’wah bil hal through social action, the strategy of da’wah bil hal through example, and the last one through the mosque.